2015
DOI: 10.1063/1.4917279
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent flow analysis in spatiotemporally chaotic 2-dimensional Kolmogorov flow

Abstract: Motivated by recent success in the dynamical systems approach to transitional flow, we study the efficiency and effectiveness of extracting simple invariant sets (recurrent flows) directly from chaotic/turbulent flows and the potential of these sets for providing predictions of certain statistics of the flow. Two-dimensional Kolmogorov flow (the 2D Navier-Stokes equations with a sinusoidal body force) is studied both over a square [0, 2π] 2 torus and a rectangular torus extended in the forcing direction. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…They are currently found through Newton-GMRES-hook iterations (see, e.g., Kawahara et al (2006);Viswanath (2007); Willis et al (2013); Lucas & Kerswell (2015)) with the drawbacks discussed in the Introduction. Alternatives include the variational method of Lan & Cvitanović (2004) which shares the universally convergent property of our adjoint-based method.…”
Section: Discussionmentioning
confidence: 99%
“…They are currently found through Newton-GMRES-hook iterations (see, e.g., Kawahara et al (2006);Viswanath (2007); Willis et al (2013); Lucas & Kerswell (2015)) with the drawbacks discussed in the Introduction. Alternatives include the variational method of Lan & Cvitanović (2004) which shares the universally convergent property of our adjoint-based method.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, properties of the ECS have something to say about how transition is triggered (Viswanath & Cvitanović 2009;Duguet et al 2010;Pringle et al 2012), the subsequent transitional process (Itano & Toh 2001;Skufca et al 2006;Schneider et al 2007;Mellibovsky et al 2009) and features of the turbulent state itself (e.g. Kawahara & Kida (2001); Hof et al (2004); Viswanath (2007); Gibson et al (2008) ;Chandler & Kerswell (2013) ;Willis et al (2013); Lucas & Kerswell (2015)). …”
Section: Introductionmentioning
confidence: 99%
“…They called this solution a unimodal solution, and suggested that at high Reynolds numbers there is at least one unimodal solution, independent of the number of jets of the original parallel flow. Note that the Kolmogorov problem has been studied from several perspectives including transition to chaos (Platt, Sirovich & Fitzmaurice 1991), the orbital instability of chaotic flow (Inubushi et al 2012) and the extraction of invariant sets from chaotic attractors (Lucas & Kerswell 2015). We will compare our results on a sphere with those of Kolmogorov flows in a planar domain.…”
Section: Introductionmentioning
confidence: 89%